Sixth Century Global Climatic Disaster, the Origins of Islam, and its World-System Consequences - Andrey Korotayev (Journal of World-Systems Research)
We suggest viewing the origins of Islam against the background of the sixth century global climatic disaster and the Arabian socio-ecological crisis that was one of its parts. Most socio-political systems of the Arabs reacted to the socio-ecological crisis by getting rid of the rigid supra-tribal political structures (kingdoms and chiefdoms) which started posing a real threat to their very survival. The decades of fighting which led to the destruction of most of the Arabian kingdoms and chiefdoms led to the elaboration of some definite “anti-royal” freedom-loving tribal ethos. At the beginning of the seventh century tribes which would recognize themselves as subjects of some terrestrial supra-tribal political authority, the “king,” risked losing its honor. However, this seems not to be applicable to the authority of another type, the “celestial” one. In the meantime the early seventh century evidences the merging of the Arabian tradition of prophecy and the Arabian Monotheist “Rahmanist” tradition which produced the Arabian prophetic movement. The Monotheist Rahmanist prophets appear to have represented a supra-tribal authority just of the type many Arab tribes were looking for at this very time, which seems to explain to a certain extent those prophets’ political success (including the extreme political success of Muhammad). The sixth century global climatic disaster influenced the world-systems development mainly through one of its logical outcomes, the formation of Islam and the formation of a colossal Islamic communication network reproduced through an annual pilgrimage to Mecca.